PETROGRAPHY OF GRANITIZIED AND BASIFICATED ROCKS OF GRANITOID INTRUSIVES' CONTACTS OF BARGUSHAT MOUNTAIN RANGE: (Syunik Region, Armenia) (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
It is stated in the article the petrographic description of contact-metasomatic granitizied and basificated rocks, structural-textural peculiarities of rare and little known types of rocks in the geological literature, form of metasomatic bodies, their internal structure and correlation with enclosing volcanic rocks of basalt-andesite composition. It is proved that the opportunity of formation of ores like granite and gabbro by the volcanic rocks of andesite-basalt composition by the contact-metasomatic granitization is possible. The described geological-petrographic data are the only objective basis for decision of petrogenesis problems of these problematic rocks.
Keywords: Armenia; Syunik Region; contact-metasomatic granitizied and basificated rocks